What’s the Point: Storytelling in Beowulf - Venables, Melissa J. (2019)
Stories which are set apart from the surrounding discourse, contain sufficient detail to engage the audience, have recognisable characters, and have a discernible point may also have the power to effect change by influencing their audiences. The purpose of this thesis is twofold: to develop a methodology that approaches stories in a way that acknowledges this power to act, and to test whether Old English narratives can be approached in this way by applying the methodology to Beowulf.